Systemic management of autoimmune anterior uveitis - Bachta, Artur; Tłustochowicz, Mateusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Autoimmune uveitis is an acute, recurrent, sight-threatening disease that can lead to severe visual loss and blindness. It requires systemic immunosuppressive therapy and continuous monitoring by ophthalmologist and rheumatologist. There are no universally accepted referral patterns for the treatment of endogenous uveitis. Most specialists indicate corticosteroids, methotrexate and cyclosporine A as the first use drugs. Anti-cytokine drugs are a new opportunity for the patients unresponsive to the conventional anti-inflammatory and immunosuppressive therapy.